PERBANDINGAN PERAN GURU DALAM NOVEL TRESNANE LEKET RING DANU BATUR DAN NOVEL BUKIT BUUNG BUKIT MENTIK - Sri Candra Dewi; I Made Sunaryana (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2020)
Balinese literature is a literary work that was born and developed in Bali. Balinese literary works as a description of the life and culture of the Balinese people. This study aims to explore the depiction of teacher figures in literary works in order to find out events related to the comparison of teacher roles contained in the Tresnané Leket Ring Danu Batur novel and the Bukit Buung Bukit Mentik novel. The type of data used in this study is qualitative data using three theories, namely the theory of structuralism, comparative literary theory and theory of meaning. The results of this study are (1) Tresnané Leket Ring Danu Batur novel and Bukit Buung Bukit Mentik novel consisting of a narrative structure which includes: incident, plot, setting, character / characterization, theme, mandate. (2) The comparison of teacher figures in literary works in the form of novels is based on the role of teachers such as teachers as designers, as movers, as motivators, and as evaluators. In the depictions of teachers in these two novels, there are several similarities and differences (3) The meaning of the teacher in these two novels such as morality, education, and sincerity. Keywords: Comparison, Role of Teacher, Novel